Registration of 'Egan' Wheat with Resistance to Orange Wheat Blossom Midge. Issue 3 (15th August 2014) - Blake, N. K.; Stougaard, R. N.; Bohannon, B.; Weaver, D. K.; Heo, H.-Y.; Lamb, P. F.; Nash, D.; Wichman, D. M.; Kephart, K. D.; Miller, J. H.; Reddy, G. V. P.; Eckhoff, J. L.; et al.
Abstract : 'Egan' hard red spring wheat ( Triticum aestivum L.) (Reg. No. 1102, PI 671855) was developed by the Montana Agricultural Experiment Station and released in 2014. Egan is intended for production in areas of Montana infested with the orange wheat blossom midge (OWBM) ( Sitodiplosis mosellana Géhin). Egan is resistant to OWBM due to antibiosis conferred by resistance gene Sm1 . Egan also contains a chromosome segment originally introgressed into wheat from T. turgidum ssp. dicoccoides containing a gene for high protein ( Gpc‐B1 ) and a gene for stripe rust (caused by Puccinia striiformis Westend. f. sp. tritici ) resistance ( Yr36 ). Egan has shown high yield potential and high grain protein in nurseries grown under OWBM pressure in the Flathead Valley of Montana. Egan is the first hard red spring wheat cultivar with resistance to OWBM developed for Montana.